E-technologies: transformation in a connected world 5th international conference, MCETECH 2011, Les Diablerets, Switzerland, January 23-26, 2011, revised selected papers - Babin, Gilbert; Stanoevska-Slabeva, Katarina; Kropf, Peter (Lecture notes in business information processing, 2011)
This volume constitutes the proceedings of the 5th International Conference on E-Technologies, MCETECH 2011, held in Les Diablerets, Switzerland, January 23-26, 2011. Originally 10 papers were selected from a total of 32 submissions. Seven additional papers were included following a second round of reviewing and improvement.The papers in this volume cover topics such as process modeling, organizational transformation, e-Business, e-Government, e-Education, and e-Health.